Dealing with the dead in ancient Egypt : the funerary business of Petebaste - Donker van Heel, K. (The American Univeristy in Cairo Press, 2021)
"Petebaste son of Peteamunip, the choachyte, or water-pourer, lived during the first half of the seventh century BCE in the reigns of the Twenty-fifth Dynasty Kushite kings Shabaka and Taharqa and was responsible for the comfortable and carefree afterlife of his deceased clients by bringing their weekly libations. But Petebaste was also responsible for a wide range of other activities--he provided a tomb to the family of the deceased, managed the costs of the personnel and commodities, and took care of all necessary paperwork, while also tending to the gruesome preparation of the mortal remains of the deceased. Drawing on an archive of eight abnormal hieratic papyri in the Louvre that deal specifically with the affairs of a single family, Donker van Heel takes a deep dive into the business dealings of this Theban mortuary priest. In intimate detail, he illuminates the final stage of the embalming and coffining process of a woman called Taperet ('Mrs. Seedcorn') on the night before she would be taken from the embalming workshop to her final resting place, providing fascinating insight into the practical day-to-day aspects of funerary practices in ancient Egypt"--